(untitled) (Revista Contexto & Educação, 2023)
Our motivation emerged from how human body is approached in formal school education by Biology and Physical Education subjects, which historically restricted it to the anatomical and physiological areas. This text explored the elaboration and application of a didactic sequence from a qualitative methodological approach in a class from the second year of the Integrated Technical High School in Chemistry, from Cefet/RJ, Valença, RJ, Brazil. The objective we presented a didactic sequence for the construction of an integrated and dynamic perception of the body. The didactic sequence is divided into three pedagogical moments: initial problematization, organization of knowledge, and application of knowledge. Data were recorded from activities developed on the Microsoft Teams®. The results and discussions were presented in three topics: students’ previous knowledge; practical activities on internal and external bodily sensations through variations in respiratory and heart rhythms; and analysis of the students in their surroundings and their intervening propositions for an integrated and collective human body. The data showed that the students initially tended to move away from the integrated perception of the body, and that, as they developed the activities, they added other perceptions beyond the biological dimension, such as self-knowledge activities, psychological well-being, environmental care and collective health.